2008
DOI: 10.1017/s0031182008004897
|View full text |Cite
|
Sign up to set email alerts
|

Spore ornamentation of Minchinia occulta n. sp. (Haplosporidia) in rock oysters Saccostrea cuccullata (Born, 1778)

Abstract: Phone 61 08 9360 24792 ABSTRACT A Minchinia sp. (Haplosporidia: Haplosporidiidae) parasite was identified infecting rock oysters and morphologically described by Hine and Thorne (2002) using light microscopy and transmission electron microscopy (TEM).The parasite was associated with up to 80% mortality in the host species and it is suspected the parasite would be a major impediment to the development of a tropical rock oyster aquaculture industry in northern Western Australia.However, attempts to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The type species, M. chitonis , has two long appendages at each end of the spore (Ball 1980), M. tapetis has only a single long aboral tail (Azevedo 2001), and M. teredinis has four unbranched appendages (McGovern and Burreson 1990). Another newly described Minchinia sp., M. occulta , is covered with a network of branching, microtubule‐like structures (Bearham et al 2008a). The spore ornamentation of M. dentali , a parasite of scaphopods in the French Mediterranean Sea, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The type species, M. chitonis , has two long appendages at each end of the spore (Ball 1980), M. tapetis has only a single long aboral tail (Azevedo 2001), and M. teredinis has four unbranched appendages (McGovern and Burreson 1990). Another newly described Minchinia sp., M. occulta , is covered with a network of branching, microtubule‐like structures (Bearham et al 2008a). The spore ornamentation of M. dentali , a parasite of scaphopods in the French Mediterranean Sea, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, NM-BG were also not reported from Minchinia occulta (Hine & Thorne 2002, Bearham et al 2008b), but vegetative stages were rarely observed. Indentations in the nuclear surface (INS) have been reported in the NZAP and 3 ostreid haplosporidians (Table 4).…”
Section: Occurrence Of Aer Nm-bg Ins and Cytoplasmic Aggregates Of mentioning
confidence: 86%
“…reported from rock oysters Saccostrea cuccullata by Hine & Thorne (2002) was reclassified as Minchinia sp. on the basis of a molecular study (Bearham et al 2007), and described as M. occulta Bearham et al (2008b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations